A Study of Human-Motifs of Ajā'ib al-Makhlūqāt wa Gharā'ib al-Mawjūdāt Manuscript (A Case Study of Ajā'ib al-Makhlūqāt wa Gharā'ib al-Mawjūdāt of Astan Quds Razavi Central Library Manuscript) - Sara Sadeghinia (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Ajā'ib al-Makhlūqāt is one of the illustrated manuscripts available in the Central Library of Astan Quds Razavi. This book was written by Qazvini in the encyclopedic order in the seventh century AH. This research has selected version 35212 from among three illustrated copies available in Astan Quds library and has examined its human-icon from among the icons. In the selected version, 23 images belong to human-images, which are classified into two categories. The first category consists of male or female constellations that appear in the period and have a natural structure, and the second category is imaginary creatures derived from myths and folk tales in the form of a combination of human-animal is depicted. The paintings are drawn in the style of the Jalayri School. Although the school was influenced by Chinese painting, it took on Iranian culture and, in addition to innovation, played an important role in the development of the Herat school, which was the pinnacle of Iranian painting. In this research, an attempt is made to investigate the degree of adaptation of the text with the drawings in the selected version. The research has a descriptive-analytical method and has been done through documentary and field research. The results show that the illustrations serve the text and help the reader to identify the text's descriptions and understand them better. Wherever the artist feels the need to break the boundary between fantasy and reality, the images are more appealing. The figures are all facing west and east, with none facing each other. The figures are usually in a frame that separates them from the text.